The Effect Of Service Quality, Product Quality On Purchasing Decisions Through Customer Satisfaction As An Intervening Variable : - - Avita Nurha Agustina; Heri Prabowo; Bayu Kurniawan (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the effect of service quality, product quality on purchasing decisions through customer satisfaction as an intervening variable at Whitebone Resto Semarang. The research method used is quantitative using SMARTPLS (Smart Partial Squares). The population in this study were Whitebone Resto Semarang customers. The sample used purposive sampling method (purposive sampling) the number of research samples was 96 respondents. The results of this study indicate that (1) Service Quality affects Customer Satisfaction, (2) Product Quality affects Customer Satisfaction, (3) Service Quality has no effect on Purchasing Decisions, (4) Product Quality affects Purchasing Decisions, (5) Customer Satisfaction affects Purchasing Decisions, (6) Service Quality affects Purchasing Decisions through Customer Satisfaction as an intervening variable, (7) Product Quality affects Purchasing Decisions through Customer Satisfaction as an intervening variable. Keywords: Service Quality, Product Quality, Customer Satisfaction, and Purchase Decision.